2005
DOI: 10.1165/rcmb.2005-0133oc
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Endothelial Signaling during Lung Expansion

Abstract: Although high tidal volume ventilation exacerbates lung injury, the mechanisms underlying the inflammatory response are not clear. Here, we exposed isolated lungs to high or low tidal volume ventilation, while perfusing lungs with whole blood, or blood depleted of leukocytes and platelets. Then, we determined signaling responses in freshly isolated lung endothelial cells by means of immunoblotting and immunofluorescence approaches. In depleted blood perfusion, high tidal volume induced modest increases in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Increased endothelial P-selectin expression and an increase in microvascular permeability are potentially proinflammatory events, since they may underlie, respectively, leukocyte recruitment (6,22) and lung water increase (23). Our findings indicate that such proinflammatory events are regulated by Cx43-determined mechanisms.…”
Section: Figurementioning
confidence: 70%
“…Increased endothelial P-selectin expression and an increase in microvascular permeability are potentially proinflammatory events, since they may underlie, respectively, leukocyte recruitment (6,22) and lung water increase (23). Our findings indicate that such proinflammatory events are regulated by Cx43-determined mechanisms.…”
Section: Figurementioning
confidence: 70%
“…These studies indicate that despite the lack of overt lung injury, as indicated by the absence of microvascular hyperpermeability, FLEC showed proinflammatory responses, including increased tyrosine phosphorylation, and expression of P-selectin (19,20). Importantly, these findings indicate that HVinduced EC stretch is itself sufficient to activate an adhesive phenotype on EC.…”
mentioning
confidence: 82%
“…Using our reported procedures (19,20), we isolated and blood-perfused rat (Sprague-Dawley, Taconic Farms, Germantown, NY) and mouse lungs. Mice were wild type (WT, C57BL/6) or genetically deficient in P-selectin (P-selectin knockout [P sel 2/2 ]) (Jackson laboratories, Bar Harbor, ME).…”
Section: Lung Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblotting of pathway signal molecules in both isolated lungs and lungs of intact mice was used to measure protein quantities and their phosphorylation state. An intact animal preparation was used because the presence of whole blood and leukocytes in the lung increased endothelial phosphorylation of intracellular proteins by more than 10-fold and better represents in vivo effects of high pressure ventilation without additional insults such as surgical manipulation of the lung (73). Acute changes in vascular permeability were evaluated using the capillary filtration coefficients (K f ) in isolated perfused lungs and using bronchoalveolar lavage (BAL) fluid albumin concentrations in intact mice.…”
mentioning
confidence: 99%